An Integrated Risk Analysis Approach in Military Hospitals: Implications for Public Health Preparedness and Resilience - Faonaso Harefa; Yahdiana Harahap; Dian Andriani Ratna Dewi; R.M. Tjahya Nurrobi; Sutanto Sutanto; Cecilia F. Harsono (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Military hospitals perform a dual function by providing healthcare services for soldiers and their families while also supporting public health needs during crises. This dual role generates complex hazards spanning biological, chemical, physical, and psychological dimensions, thereby requiring a comprehensive risk analysis framework. The objective of this study is to develop an integrated risk analysis approach comprising risk assessment, risk management, and risk communicationto strengthen occupational safety in military hospitals, with broader relevance for public health and global health security. Methods: A mixed methods design was applied. Data were collected through direct observation and in-depth interviews with healthcare personnel, complemented by a structured survey using standardized questionnaires. Qualitative analysis was conducted using NVivo 12 and quantitative analysis using SEM PLS-4. The study involved 100 respondents comprising medical personnel, health workers, and staff at Rumah Sakit Pusat Pertahanan Negara (RSPPN) and Pusat Kesehatan TNI, selected through random sampling. Results: Qualitative findings derived from NVivo 12 analysis revealed a multidimensional hazard spectrum characterized by weak cross sectoral coordination, limited personnel capacity, and insufficient integration among risk analysis components. Quantitative analysis using SEM PLS-4 further confirmed that Integrated Risk Analysis has a positive and statistically significant effect on Public Health Preparedness and Community Resilience (T-statistic = 11.046 > 1.96; p-value < 0.05); and F-square (0.18- efect moderat). Conclusion: This study concludes that Integrated Risk Analysis exerts a significant influence on public health preparedness and community resilience in military hospitals. The findings underscore the necessity of strengthening management, integration, and cross sectoral communication. Nonetheless, the contextual limitations regarding research setting and sample size suggest the need for future studies with broader scope and institutional diversity to reinforce the generalizability of the findings.